Blockchain in health sciences: Research trends in Scopus - Araujo-Inastrilla, Carlos Rafael; Vitón-Castillo, Adrián Alejandro (Iberoamerican Journal of Science Measurement and Communication, 2023)
Objective. The scientific production indexed in Scopus on Blockchain in health sciences was characterized from 2012 to 2021. Design/Methodology/Approach. A bibliometric study of the scientific production related to Blockchain technology in health sciences was carried out and indexed in Scopus from 2012 to 2021. Bibliometric indicators of productivity, impact, and collaboration were used. The SciVal, VOSviewer, and Microsoft Excel tools were used to process and present the information. Results/Discussion. Between 2012 and 2021, 1,543 articles were published on the subject studied, with an average of 14.9 citations per publication. Scientific production increased until 2021, as did the number of authors. International collaboration fluctuated. The most frequent terms related to Blockchain were the Internet of Things, smart contracts, and cryptography. India, China, and the United States led the collaborations, and authors of Asian origin predominated. Conclusions. The scientific production of Blockchain in health has grown due to its transformative potential in health systems, with an interest in the security and traceability of medical data.